Carbon Storage Estimation in the Sungai Buluh Peat Forest Reserve, Mandahara Ulu District, Tanjung Jabung Timur Regency - Dinanty, Fawwaz; Nursanti, Nursanti; Nahlunnisa, Hafizah; Nazri Yandi, Wahyu (Jurnal Biologi Tropis, 2025)
Indonesia has the third-largest tropical forest area in the world, making it a key player in global climate change mitigation efforts. This study aims to identify tree species and estimate above-ground carbon (AGC) stocks in the Sungai Buluh Peat Protected Forest, Jambi. The research employed a descriptive quantitative approach using permanent plot methods and allometric equations across 30 plots measuring 20×20 meters. Data collected included tree species, diameter, and height, which were then analyzed to calculate biomass and carbon stocks. The results identified 1,140 individuals from 26 species, with Mangifera parvifolia, Dyospyros siamang, and Madhuca modleyana being the most dominant. The stand volume reached 426.11 m³/ha, while the estimated AGC was 173.96 tons/ha. The majority of the carbon stock was contributed by the tree strata, accounting for more than 73%. These findings highlight the importance of conserving peatland forests as long-term carbon reservoirs.